2016
DOI: 10.3319/tao.2016.06.13.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Extreme Rainfall Changes over Taiwan Using a Standardized Index

Abstract: The annual daily maximum precipitation (rx1day) is widely used to represent extreme events and is an important parameter in climate change studies. However, the climate variability in rx1day is sensitive to outliers and has difficulty representing the characteristics of large areas. We propose to use the probability index (PI), based on the cumulative density function (CDF) of a generalized extreme value (GEV) distribution to fit and standardize the rx1day to represent extreme event records in this study. A go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Taiwan's annual island-average extreme rainfall has been increasing (Chen et al 2007;Shiu et al 2009;Tung et al 2016;Wu et al 2019), especially since the year 2000 (Chang et al 2013;Tung et al 2016;Liang et al 2017). In this next section, we will follow two complementary approaches for defining and calculating ER trends.…”
Section: Trends In Extreme Rainfallmentioning
confidence: 99%
“…Taiwan's annual island-average extreme rainfall has been increasing (Chen et al 2007;Shiu et al 2009;Tung et al 2016;Wu et al 2019), especially since the year 2000 (Chang et al 2013;Tung et al 2016;Liang et al 2017). In this next section, we will follow two complementary approaches for defining and calculating ER trends.…”
Section: Trends In Extreme Rainfallmentioning
confidence: 99%
“…After referring to Khattab and Levetin (2008) regarding sampling height difference and fungal spore concentration, the Aspergillus/Penicillium concentration in the present study was expected to be lower because of the higher sampling height (15 m above the ground) than that used by Chen et al (2.5 m above the ground); however, our results revealed a higher Aspergillus/Penicillium concentration. The possible reasons for this result include different sampling locations, nearby land utilization, and changes in meteorological and environmental conditions over the past few years, as has been reported by many studies (Ding et al, 2016;Kuo et al, 2016;TCCIP, 2016;Tung et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Precipitation is one of the critical parameters that climate change will influence and that will induce risk, hence the following were studied in great detail in Taiwan: the land-sea breeze system that that facilitates the formation of diurnal rainfall events [34][35][36], and seasonal monsoon events, including Madden-Julian oscillation impacts on winter rainfalls, and the East Asian summer monsoon (aka Meiyu), under different climate scenarios [37,38]. The preliminary study of watershed typhoon rainfalls and extreme precipitation under climate change found that the 24-h duration precipitation depth for 20-year and 100-year extreme events are likely to increase, suggesting concerns about the current hydrologic designs of critical infrastructures [39][40][41][42]. The secondary effects of precipitation on several factors, such as landslides, where critical precipitation is a characteristic that triggers large-scale landslide events, were studied and considered in conjunction in order to understand the cause/effect relationships; they were also impact assessed using climate projection [43][44][45][46][47].…”
Section: Adaptation Research Policy Support and Advocacymentioning
confidence: 99%